Mini-Review: GSDME-Mediated Pyroptosis in Diabetic Nephropathy - Li, Wen; Sun, Jing; Zhou, Xiaoxi; Lu, Yue; Cui, Wenpeng; Miao, Lining (Frontiers in Pharmacology, 2021)
Pyroptosis, a newly identified type of lytic programmed cell death (PCD), is featured in pore formation in the plasma membrane, swelling, and cell rupture with secretion of cellular contents, especially the inflammatory cytokines. A large number of studies have shown that pyroptosis includes not only the GSDMD involved caspase-1-dependent classical pathway and caspase-11/4/5-dependent non-classical pathway, but also the GSDME involved caspase-3 (Casp3) dependent pathway. Diabetic nephropathy (DN) is one of the most serious microvascular complications in diabetes. Present evidence suggestes that pyroptosis promotes the progression of several diabetic complications including DN. The underlying mechanism mediating renoprotection conferred by GSDME regulation in the diabetic kidney, specifically in human tubular cells has been investigated. Z-DEVD-FMK, the inhibitor of Casp3, ameliorated albuminuria, renal function, and tubulointerstitial fibrosis in diabetic mice. The nephroprotection mediated by Z-DEVDFMK was potentially associated with inhibition of GSDME. In vitro, molecular and morphological features of secondary necrosis were observed in glucose-stimulated HK-2 cells, evidenced by active GSDME cleavage, ballooning of the cell membrane, and release of cellular contents. Based on this, it is not difficult to conclude that therapies targeting Casp3/GSDME dependent pyroptosis show great application prospects in DN, and novel nephroprotective strategy using GSDME-derived peptides directed against Casp3-induced cell death in vitro and in vivo may be a key breakthrough for this goal. Therefore, in the mini-review, we introduced the history of pyroptosis; gasdermin family proteins especially GSDME, and GSDME mediated pyroptosis in DN, expecting this novel mechanism may provide valuable therapeutic insights for the treatment of DN.